An azorean dairy farms typology - Silva, Emiliana (2005)
The objective of this paper was to define types of Azorean farms from a panel data of 174 farms of The European database of Farm Accountancy Data Network of the Azores, Portugal. This study used cluster analysis, the Ward method. The results, allowed the identification of three types of grazing systems of dairy farms as follows: 1) extensive grazing systems (less than smaller 1.4 cows per hectare); 2) moderate intensive grazing system (1.4 to 2.4 cows per hectare); and 3) intensive grazing system (more than 2.4 cows per hectare).